GANDHIAN PHILOSOPHY AND ITS RELEVANCE IN MODERN TIMES - Patel, Bhagvati; Dhurve, Kanhaiya Lal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Principles are the basic pillars of human knowledge and behaviour, which help in understanding life, organising society and walking on the path of progress. Principle is the fundamental rule or concept of any subject, subject matter or idea, which is systematically and logically proven. It is such a fundamental truth which is considered true on the basis of logic and experience. Principles are equally applicable in all situations and present any knowledge in a systematic and organised form. Principles also inspire new discoveries and ideas and pave the way for their solution by analysing the problems. These principles are of different types such as personal, social, ethical, philosophical, spiritual, scientific etc. When any person or great man propounds some rules or formulas for the purpose of public welfare, common welfare or social reform, then such rules are called personal principles. Such as the principles propounded by Mahatma Gandhi, which are based on the thoughts and philosophy of Gandhiji, which are centered on truth, non-violence, simplicity, self-rule, self-reliance, social justice, and the sambhava of all religions. These principles provide a moral and practical guide for individual and collective life. They provide stability and clarity to a person in his life and prove helpful in taking decisions in difficult situations